Literature Review: Application of Montessori Method in the Formation of Independent Character in Early Childhood - Siti Fauziah; Herman Nirwana; Dina Sukma (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Early childhood education plays an important role as a basis for character formation and the development of children's knowledge, abilities and skills. One of the characters that influences the development of early childhood is independence. Independence is a behavior characterized by self-confidence, the ability to take the initiative, the ability to overcome problems or obstacles faced and do something independently without the help of others. Independence in everyday life means being able to stand alone without relying on others. However, in reality in the field, many early childhood children are still found to be not independent in doing something, this can be seen from the attitudes and behavior displayed by children in the form of children who find it difficult to adapt to the environment, have a rigid personality, children tend to be unconfident and unable to complete their life tasks well. So it is important to foster independence in children from an early age, by using the Montessori method which allows children to develop at their own pace. This method gives children the freedom to choose the activities they want, so they can learn and play according to their interests. Therefore, researchers are interested in conducting a literature review on the application of the Montessori method in the formation of independent character in early childhood. Literature review conducted by researchers using publications from 2019-2024 which can be accessed in full text in pdf format and scholarly (peer reviewed journals) using google schoolar, so that 10 articles were found that had been screened according to the discussion of the article raised.